Intracranial hemorrhagic vasculitis in a child with varicella zoster virus infection: a case report - Saket Satyasham Toshniwal; Jiwan Kinkar; Anand Loya; Palash Sandeep Kotak; Sourya Acharya; Anil Wanjari (Frontiers in Medicine)
BackgroundVaricella zoster virus (VZV) infection is a common viral illness in children, typically manifesting as chickenpox and having a benign, self-limiting course. However, severe neurological complications—such as vasculitis resulting in intracranial hemorrhage—although rare, can occur and are associated with significant morbidity and mortality.Case presentationWe present the case of a previously healthy 7-year-old boy who developed intracranial hemorrhagic vasculitis 14 days after a primary VZV infection. The child experienced sudden-onset seizures and altered sensorium. Neuroimaging showed an intracranial hemorrhage with evidence of cerebral vasculitis. Laboratory tests, cerebrospinal fluid (CSF) analysis, and serological studies confirmed a recent VZV infection. The patient was treated with antiviral therapy and corticosteroids, resulting in improvement.DiscussionThis case illustrates a rare but severe vascular complication of VZV infection in children. The pathophysiology is viral-induced inflammation of the vessels, leading to vessel wall damage, necrosis, and possible hemorrhage. Early detection through clinical suspicion, imaging, and CSF examination is essential for starting early treatment, which can change the course of the disease and improve outcomes.ConclusionIntracranial hemorrhagic vasculitis is an uncommon but serious complication of VZV infection in children. This case highlights the need to consider post-infectious vasculitis in the differential diagnosis of any child with acute neurological symptoms and a recent history of chickenpox to avoid delays in diagnosis and management.